The whispering dead - Coates, Darcy (Coates, Darcy. Gravekeeper, 2021)
"When Keira wakes in a strange forest, she can remember only two things: she can see ghosts, and strange, mask-wearing men are hunting her. She seeks shelter at a church, and the kind pastor offers to let her stay in the groundskeeper's cottage for a few days. But the cottage is situated behind the graveyard, and its spirits are only too eager to make themselves known. This sleepy, quaint town has dark secrets from the past that continue to haunt in increasingly terrifying ways. Keira's shocked to discover her lost memories may be woven through the town's bizarre hauntings, and soon, she's thrown full-tilt into a race to unravel the decades-old mystery... before it's too late"--